KEEFEKTIFAN PENGGUNAAN MODEL MID (Meaningful instruksional Design) TERHADAP KETERAMPILAN MENULIS CERITA PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS 5 SEKOLAH DASAR - Dian Permatasari Kusuma Dayu (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
The learning process that takes place in the form of learning involves two parties between teachers and students that aims to improve student learning outcomes. In learning language there are four skills namely listening, speaking, reading, and writing. Among the four skills, writing skills is regarded as the most difficult language skills. Writing Skills is one language skills that must be mastered by the student. Civilizing expressing ideas or students' ideas in written form can be developed through education. However, unfortunately this habituation is not taken seriously in the education system, so that the culture of writing in the student still low and there are still many students who find it difficult to carry out writing stories. Thus to overcome these difficulties using model MID (meaningfull instructional design).Keywords: Writing Skills, Model MID, Indonesian.